Monitoring of an underwater disposal site (rouillard pond, France) after completion of filling - Moilleron, R.; Carpentier, S.; Thevenot, D.R. (Remediation of Contaminated Sediments – 2003: Proceedings of the Second International Conference on Remediation of Contaminated Sediments, 2003)
This study deals with the monitoring of an underwater disposal site, the Rouillard pond (RP), from the time of discharge to deposition of dredged sediments. The monitoring of the RP surface water revealed that the most important features of the DM dumping used was the increase in suspended matter (SPM) concentration. In addition to this direct effect, a nutrient release, more specifically ammonium and, to a lesser extent, dissolved organic carbon (DOC) release were observed. Besides, we did not observe any organic micro-pollutant or trace metal release in the RP surface water so far. Based on our observations, it is likely that eutrophication is still occurring in the Rouillard pond but at a lower rate than during the dumping period. Evidence for such processes came both from the determination of the benthic community composition and the calculation of diatom indices, in September 2002, i.e. one year after the filling had ceased. Moreover, no significant emission of RP sediment pore water compounds towards the surface water has been observed yet.